2020
DOI: 10.1016/j.envpol.2020.115184
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long-term exposure to microfibers on ecosystem services provided by coastal mussels

Abstract: The biofiltration capacity of bivalve populations is known to alleviate the effects of coastal eutrophication. However, this important ecosystem service could potentially be impaired by the increasing microplastic abundance in near shore environments. It is known that relatively large microplastics (~500µm) impair the filtration capacity of bivalves, however, the effect of smaller microplastics, and specifically microfibers, is not known even though they are more common in many natural systems and similar in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…3 and Online Resource 1 for time-lapse movie), which have become a world-wide concern. Since early reports about microplastic contamination in mussels (Browne et al 2008;von Moos et al 2012;Wegner et al 2012), an increasing number of papers have been published, mainly on species of Mytilus and Perna (Chae and An 2020; Gedik and Eryasar 2020; Kazour and Amara 2020; Piarulli and Airoldi 2020; Christoforou et al 2020;Cole et al 2020;Li et al 2020a;Stamataki et al2020;Wakkaf et al 2020;Webb et al 2020;Alnajar et al 2021;Cappello et al 2021;Cho et al 2021;Klasios et al 2021;Kumar et al 2021;Liu et al 2021;Perez et al 2021;Seuront et al 2021;Wang et al 2021a,b). Considering their distributions around cities and other human habitations, mussels are ideal organisms for monitoring microplastic pollution.…”
Section: Ingestion Of Microplasticsmentioning
confidence: 99%
“…3 and Online Resource 1 for time-lapse movie), which have become a world-wide concern. Since early reports about microplastic contamination in mussels (Browne et al 2008;von Moos et al 2012;Wegner et al 2012), an increasing number of papers have been published, mainly on species of Mytilus and Perna (Chae and An 2020; Gedik and Eryasar 2020; Kazour and Amara 2020; Piarulli and Airoldi 2020; Christoforou et al 2020;Cole et al 2020;Li et al 2020a;Stamataki et al2020;Wakkaf et al 2020;Webb et al 2020;Alnajar et al 2021;Cappello et al 2021;Cho et al 2021;Klasios et al 2021;Kumar et al 2021;Liu et al 2021;Perez et al 2021;Seuront et al 2021;Wang et al 2021a,b). Considering their distributions around cities and other human habitations, mussels are ideal organisms for monitoring microplastic pollution.…”
Section: Ingestion Of Microplasticsmentioning
confidence: 99%
“…Polyester and PET fibers are commonly used in textiles, and nylon (polyamide) is another common polymer used in textiles, fishing gear, and other maritime equipment (Browne et al, 2011; Mishra et al, 2019). Both polymers are prevalent in the environment and have shown negative effects on aquatic organisms, such as changes in molting behavior and prey selectivity of juvenile copepods (Cole et al, 2019) and decreased filtration capacity and filtration rates of mussels (Christoforou et al, 2020; Woods et al, 2018). For the development of the paraffin microtomy method described, spools of multifilament synthetic fibers (PET‐ES305710 and nylon 6,6‐AM325705) were purchased commercially from Goodfellow.…”
Section: Methodsmentioning
confidence: 99%
“…The only prior method for making sufficient quantities of uniform microfibers ≤100 µm for laboratory experiments used a cryogenic microtome to thinly slice embedded multifilament polymer fibers (Cole, 2016). This method is more precise than other methods, is appropriate for laboratory experiments, and produces microfibers that are easily distinguishable from airborne contaminants (Christoforou et al, 2020). Although it generates high‐quality experimental microfibers, the cryomicrotomy method is time‐consuming and requires the use of a relatively uncommon instrument: a cryogenic microtome (Christoforou et al, 2020; Cole, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that, like larger MP spheres, MP fibers may be largely eliminated via biodeposits. Recent studies with mussels indicated significant decreases in water filtration and clearance rates after 39 days of exposure to nylon fibers (35 mm long) (Christoforou et al, 2020). These kinds of studies, as well as careful reviews of research related to carbon nanotubes, are important for characterizing the potential fate and impacts of MP and NP fibers.…”
Section: Precautionary Notesmentioning
confidence: 99%